2002
DOI: 10.1007/s10096-001-0683-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative, Clinico-Epidemiologic Study of Schistosoma mansoni Infections in Travellers and Immigrants in Spain

Abstract: The study presented here aimed to contrast the marked clinical differences in the presentation of Schistosoma mansoni-induced infection between immigrants and travellers entering Spain from endemic regions, and to elucidate the therapeutic implications of these infections. A total of 200 African immigrants and 80 travellers with schistosomiasis were included in the study. Among the immigrants, 25 patients were diagnosed with Schistosoma mansoni infection; 15 presented with nonspecific symptoms, and 10 were asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 6 publications
2
19
1
7
Order By: Relevance
“…The ELISA for MAMA permits the diagnosis of only 55 to 83% of the cases caused by S. haematobium (3,19). This fact limits the potential of using only one of these ELISAs for the diagnosis of imported schistosomiasis, especially among travelers and immigrants coming from Africa (9,26). In contrast with ELISAs using microsomal antigens, the ELISA in our study revealed no differences in the diagnostic results for patients infected with S. mansoni and S. haematobium.…”
Section: Figcontrasting
confidence: 59%
See 1 more Smart Citation
“…The ELISA for MAMA permits the diagnosis of only 55 to 83% of the cases caused by S. haematobium (3,19). This fact limits the potential of using only one of these ELISAs for the diagnosis of imported schistosomiasis, especially among travelers and immigrants coming from Africa (9,26). In contrast with ELISAs using microsomal antigens, the ELISA in our study revealed no differences in the diagnostic results for patients infected with S. mansoni and S. haematobium.…”
Section: Figcontrasting
confidence: 59%
“…In recent years, immigration and the increase in travel from highrisk areas have led to an increase in the number of imported cases. Some studies indicate that 15% of immigrants and 2.5% of the travelers from areas where schistosomiasis is endemic have schistosomiasis (26). The species most commonly implicated are Schistosoma mansoni, Schistosoma haematobium, and Schistosoma intercalatum.…”
mentioning
confidence: 99%
“…It is also due to political and economic contacts with Egypt, and to the thousands pilgrims who flow through the country on their travel between Mecca and the West African countries where the disease is known to be endemic. In recent years, immigration and the increase in travel from high-risk areas have led to an increase in the number of imported cases [66].…”
Section: Schistosomiasis In Sudanmentioning
confidence: 99%
“…The country of origin was associated with specific diseases, and higher eosinophilic counts (median 1000×10 9 μL) were seen with filariasis (15). A Spanish study by Roca et al (16) found 200 cases (15.2%) of schistosomiasis among 1321 African immigrants, almost 50% of whom were asymptomatic and 30% had nonspecific abdominal pain. Female genital schistosomiasis is a frequent complication in women with urinary or systemic schistosomiasis, and it may go undiagnosed in nonendemic countries where physicians are unlikely to be familiar with this syndrome (17).…”
mentioning
confidence: 98%